Systematically Improving Your Collaboration Practice in the 21st Century - Zahn, Doug (Promoting Statistical Practice and Collaboration in Developing Countries, 2022)
This chapter explores two processes for improving a practice: POWER: A guide to successful meetings and RAPID: A guide to rapidly recover from breakdowns. Getting prepared for a conversation is one thing. The open segment is comprised of four distinct conversations: time, wanted, willing, and able. There are three foundations of the POWER process: relationship, listening, and speaking. A synergistic relationship is stronger than a working relationship by virtue of producing higher-quality results because of the trust developed in each other. Volumes have been written on "the art of conversation" and for good reason: thoughtful conversation is the foundation of successful communication. Breakdowns provide signals that the relationship or interaction needs attention, care, or understanding.